Is it possible to force people to be vaccinated? Nudge against coronavirus - Cárdenas Krenz, Ronald (Acta Bioethica, 2022)
We all know that the world is facing a terrible pandemic. Science, with effort and promptness, has been able to develop various vaccines against Covid-19, generating great expectations. However, mass vaccination processes have not advanced at the required speed due to various factors; one of the main ones is the resistance of many people to get vaccinated, for different reasons. Faced with this situation, it has oscillated between carrying out advertising campaigns to proposals for forced imposition. An alternative to go beyond the merely lyrical and coercive is to generate forms of motivation for those people to voluntarily decide to be vaccinated through various measures, direct and indirect, appealing to "Nudge" -or the "little push theory" - in order to promote the best protection of individual and collective health, the subject of this article, based on the bibliographic review on the matter and various experiences in the fight against coronavirus.